Creativity in the Lille metropolitan area: the example of the image sector - Lusso Bruno (European Regional Science Association (ERSA), 2011)
In France, the Paris region is the traditional centre for decision-making and creative functions. Unsurprisingly, it concentrates most cultural industries - cinema, multimedia, TV, etc. The aim of this paper is to study how other French cities, and more specifically regional medium-sized cities, can develop this type of activities. We will take the example of the multimedia industry in the Lille metropolitan area. Ann-Lee Saxenian (1994) has shown the importance of regional culture and heritage in the constitution of an economic trajectory. The pre-existence of links between film production, media or microelectronic industries, and of an intense cultural life can support the emergence of essential know-how for the development of an image sector (Sträter, 2000). Lille isn't a traditional filming area and the weak presence of the television media didn't facilitate the emergence of large regional production groups. But, the decline of textile factories has allowed the development of new activities, as mail-order selling, which have used multimedia and image technologies since the 1980s. Moreover, Lille metropolitan area has a broad training offering in the technical and creative fields which can have significant repercussions for the constitution of a creative class (Florida, 2002). But the emergence of start-up has been very limited since the 1990s and 2000s. In 2009, the Lille metropolitan area counts only 350 firms in the image sector and has not a critical mass. Cognitive diversity generated by a social group stimulates creative individual potential (Miliken, Bartel and Kurtzberg, 2003). This explains the choice made by public authorities to locate audiovisual and multimedia firms in three media districts, which accommodates schools, research centres, publics authorities and firms (thanks to free tax zones, cheap facilities and incubators) according to the Triple Helix principles (Etzkowitz and Leydersdorff, 1997). That projects aim to retain young graduates by offering an environment enable to developing their careers. But the national project for extending the Plaine Saint-Denis audiovisual cluster, located north of Paris, is likely to deter the settlement of firms in Lille, because of the weakness of both the sector and the networks.
Keywords: 330